2022
DOI: 10.3390/ani12030301
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Virulence Factors in Enterotoxin-Producing Staphylococcus aureus from Bulk Tank Milk

Abstract: Staphylococcus aureus, a persistent mastitis-causing pathogen, produces various virulence factors, including enterotoxins. This study analyzed the genetic characteristics of bovine-mastitis-related virulence factors to evaluate the potential pathogenesis of S. aureus isolated from bulk tank milk. Among 93 S. aureus isolates from 396 dairy farms operated by 3 dairy companies in Korea, 40 (43.0%) isolates carried one or more enterotoxin genes. Moreover, S. aureus carrying enterotoxin genes showed a higher preval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…These data confirm the virulence of these strains. Among the classic enterotoxins, SEB and SEE have been associated with infectious strains of bovine origin, mainly ST188 [36,37]. Therefore a low occurrence of those toxins amongst our isolates was expected.…”
Section: Discussionmentioning
confidence: 87%
“…These data confirm the virulence of these strains. Among the classic enterotoxins, SEB and SEE have been associated with infectious strains of bovine origin, mainly ST188 [36,37]. Therefore a low occurrence of those toxins amongst our isolates was expected.…”
Section: Discussionmentioning
confidence: 87%
“…This data confirms the virulence of these strains. Among the classic enterotoxins, SEB and SEE have been associated with infectious strains of bovine origin, mainly of ST188 [36,37]. Therefore it can be expected a low prevalence of those toxins amongst our isolates.…”
Section: Discussionmentioning
confidence: 88%
“…Also, incomplete egc variants lacking any of the genes have been found. Thus, Song et al [37] reported a 39.5% of egc strains lacking seu. In another study, most of the isolates of swine origin possessed an incomplete egc, lacking two of the genes [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, six outbreaks of SEE poisoning occurred in France at the end of 2009, where the consumption of soft cheese made from unpasteurized milk was the common source (Ostyn et al, 2010). Furthermore, the see gene was widely found in bulk milk tanks during an investigation in South Korea, even though the authors evidenced that this gene was not detected or detected at a low frequency in milk in previous studies (Jung & Lee, 2022). This result can be related to a temperature above 8 °C, as refrigeration failures during Semina: Ciênc.…”
Section: Resultsmentioning
confidence: 93%